Revision of Chinese crickets of the tribe Modicogryllini Otte & Alexander, 1983 with notes on relevant taxa (Orthoptera: Gryllidae; Gryllinae) - Ma, Libin; Zheng, Yanna; Qiao, Min (Zootaxa, 2021)
The article revised most species of genera of Modicogryllus Chopard, 1961, Gryllodinus Bolívar, 1927, Eumodicogryllus Gorochov, 1986, Svercacheta Gorochov, 1993 and Turanogryllus Tarbinsky, 1940 and proposed a new species, Gryllodinus jijilacus sp. nov., four synonyms, Mirigryllus He, 2020 syn. nov., Gryllus bordigalensis (=Eumodicogryllus bordigalensis) Latreille, 1804 syn. nov., Gryllus chivensis (=Eumodicogryllus chivensis) Tarbinsky, 1930 syn. nov. and Gryllopsis aelleni (=Turanogryllus aelleni) Chopard, 1954 syn. nov., seven new combinations, Modicogryllus (Modicogryllus) nigrus (He, 2020) comb. nov., Mitius vaturu (Otte & Cowper, 2007) comb. nov., Loxoblemmus abrictos (Otte, 2007) comb. nov., Modicogryllus (Promodicogryllus) nigericus (Chopard, 1961) comb. nov., Eumodicogryllus chinensis (Weber, 1801) comb. nov., Eumodicogryllus vicinus (Chopard, 1968) comb. nov. and Svercacheta semiobscurus (Chopard, 1961) comb. nov., and re-established a species, Modicogryllus (Modicogryllus) latefasciatus (Chopard, 1933), as well as redescribed species of Modicogryllus (Promodicogryllus) consobrinus (Saussure, 1877), Svercacheta siamensis (Chopard, 1961) and Turanogryllus lateralis (Fieber, 1853).